2020
DOI: 10.1039/d0qo01109f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of maleimide fused benzocarbazoles and imidazo[1,2-a]pyridines via rhodium(iii)-catalyzed [4 + 2] oxidative cycloaddition

Abstract: In this paper, an efficient and sustainable synthesis of the synthetically and pharmaceutically significant maleimide-fused benzocarbazoles/imidazo[1,2-a]pyridines from the reaction of 2-arylindoles/2-arylimidazo[1,2-a]pyridines with maleimides through rhodium-catalyzed oxidative [4 + 2] annulation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…In 2020, Fan, Zhang and Li continued to apply maleimides as substrates for the Rh-catalysed CDC reaction of heterocycles (Scheme 37). 55 Apart from the 2-arylindazoles, 2-arylindoles and 2-arylimidazo[1,2- a ]pyridines were employed to afford the maleimide-fused benzocarbazoles/imidazo[1,2- a ]pyridines, which are pharmaceutically useful compounds.…”
Section: Cross-dehydrogenative Coupling Of Alkenesmentioning
confidence: 99%
“…In 2020, Fan, Zhang and Li continued to apply maleimides as substrates for the Rh-catalysed CDC reaction of heterocycles (Scheme 37). 55 Apart from the 2-arylindazoles, 2-arylindoles and 2-arylimidazo[1,2- a ]pyridines were employed to afford the maleimide-fused benzocarbazoles/imidazo[1,2- a ]pyridines, which are pharmaceutically useful compounds.…”
Section: Cross-dehydrogenative Coupling Of Alkenesmentioning
confidence: 99%
“…For instance, in 2020, Fan and co-workers developed a Rh­(III)-catalyzed [4 + 2] annulation of indoles with maleimides, delivering diverse carbazoles in high yields . Very recently, the Shi group reported an elegant intermolecular cyclization of indoles and dihydroisobenzofurans for the synthesis of indolyl benzo­[ b ]­carbazoles under mild reaction conditions . However, some of these cases were overly dependent on highly prefunctionalized aromatics, or some protocols required harsh reaction conditions, which caused a negative effect on the following applications.…”
mentioning
confidence: 99%
“…9 Very recently, the Shi group reported an elegant intermolecular cyclization of indoles and dihydroisobenzofurans for the synthesis of indolyl benzo [b]carbazoles under mild reaction conditions. 10 However, some of these cases were overly dependent on highly prefunctionalized aromatics, or some protocols required harsh reaction conditions, which caused a negative effect on the following applications. At this point, developing more direct approaches for the precise construction of polycyclic carbazoles from readily available substrates under extremely mild reaction conditions is still highly demanded.…”
mentioning
confidence: 99%
“…2-Arylindoles, a class of important and versatile building blocks, have found wide applications in organic and medicinal chemistry . The transition-metal-catalyzed cascade C–H activation and cyclization of 2-arylindoles with various activated coupling partners such as ketene, sulfoxonium ylide, benzoquinone, and maleimide have been well developed for the preparation of five- and six-membered indole-fused heterocycles. In contrast, the use of allyl alcohols as a coupling partner in the synthesis of seven-membered N-heterocyclic compounds remains elusive. In 2017, Dong et al reported a Ru-catalyzed cascade C–H allylation and oxidative annulation of 2-phenylindoles with allyl carbonates (Scheme a) .…”
mentioning
confidence: 99%
“… Due to the less electrophilic and higher steric hindrance of ketones than aldehydes, the subsequent nucleophilic addition/cyclization process was potentially affected. Although the expected cyclized product was not obtained, the reaction was interesting since almost all the C–H functionalizations involving 2-arylindoles reported to date afforded cyclization products. Thus, other α-substituted allyl alcohols such as 2f and 2g were further investigated. As excepted, 2f also reacted with 1a smoothly to afford the corresponding alkylated and alkenylated products 3af and 3af′ in reasonable yields.…”
mentioning
confidence: 99%